Implementasi Internet of Things (IoT) pada SMK AL Hikmah 2 dalam mendukung Revolusi Industri 4.0 - Aulia Desy Aulia Nur Utomo; Anggi Zafia; Bita Parga Zen; Dimas Fanny Hebrasianto Permadi; Henri Tantyoko; Yoso Adi Setyoko (LPPM IT Telkom Purwokerto, 2023)
In order to increase knowledge about technology, especially in the field of information technology, material debriefing on the Internet of Things (IoT) is conducted at Pondok Pesantren Al-Hikmah 2. The purpose of this material debriefing is important for the development of students in their learning material to support the Information Technology learning syllabus . In addition, as an illustration of the implementation of IoT applied in the industry. The delivery method is by delivering basic theory, workshops and implementation. The activity was carried out in the classroom of SMK AL-Hikmah 2 Sirampog, Brebes and was attended by 60 participants. Participants are trained on using microcontrollers as well as sensors and IoT devices. The participants were very enthusiastic about holding this training and workshop, as seen from the results of the participant satisfaction questionnaire which showed that the average answer was very satisfied as many as 31 students and 29 students answered they were satisfied with this training.